2012
DOI: 10.1017/s0950268812002087
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of novelLeptospiraserovars: a need for adjusting vaccination policies for dogs?

Abstract: A total of 855 sera from dogs in Greece were tested for antibodies to strains belonging to the Pomona, Grippotyphosa and Australis serogroups of Leptospira to assess exposure levels to these serogroups, possible associations with clinical disease and to evaluate whether these findings support the inclusion of additional serovars in dog vaccines. Antibodies were detected in 110 (12·9%) dogs. The highest seroprevalence (4·9%) was to the proposed novel serovar Altodouro belonging to the Pomona serogroup. This ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
23
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 27 publications
4
23
0
4
Order By: Relevance
“…This is in accordance with previous reports (Arent and others 2013, Renaud and others 2013). This low cut-off was chosen because the MAT has high specificity in convalescent samples, in which anti-leptospiral IgG predominates (Chernukha and others 1976).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is in accordance with previous reports (Arent and others 2013, Renaud and others 2013). This low cut-off was chosen because the MAT has high specificity in convalescent samples, in which anti-leptospiral IgG predominates (Chernukha and others 1976).…”
Section: Discussionsupporting
confidence: 94%
“…In a study from Germany, 14 per cent of dogs with confirmed leptospirosis had antibody titres to serogroup Pomona (Mayer-Scholl and others 2013). Antibodies to serovar Altodouro were also significantly associated with the presence of clinical disease in a cohort of Greek dogs (Arent and others 2013). It has therefore been suggested that inclusion of serogroup Pomona into future vaccines should be considered (Arent and others 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Serovar Altodouro, a new serovar from the Leptospira kirschneri genospecies, was recently isolated from a Mus musculus rodent species in the Trás-os-Montes region [1,16]. Later studies in dogs from Greece [17] have shown that this serovar seems highly reactive, which, in addition to our findings, may indicate the need to include serovar Altodouro as antigen in coming leptospirosis serological studies across Europe, concerning both domestic and wild populations. Several other strains from the Pomona group have been previously isolated in Portugal: serovar Mozdok strains from pigs [18] and small mammals [19], and serovar Tsaratsovo from horses [20].…”
supporting
confidence: 64%
“…Some of them, particularly serovars belonging to L. interrogans species such as serovar Pomona, have been shown to be significant domestic animal pathogens, maintained by pigs (8). However, serogroup Pomona strains clustered in L. kirschneri species, like serovars Mozdok and Altodouro, are maintained by small rodents, although they may also occasionally cause disease in domestic animals (2,13,18). Taking into account all the above data and the fact that bacteriological studies are limited in Poland, definitive comments on the epidemiology of serogroup Pomona infections in animals will require further investigations, as this can only be assessed by renal culture, which was not part of this study.…”
Section: Discussionmentioning
confidence: 99%